2012
DOI: 10.4172/1948-5956.s3-007
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Chemoprevention Targeting High Risk Populations: Model for Trial Design and Outcome Measures

Abstract: Inspite of the large number of promising nutrient-derived agents demonstrating promise as potential chemopreventive agents, most have failed to prove effectiveness in clinical trials. Critical requirements for moving nutrient-derived agents to recommendation for clinical use include adopting a systematic, molecular-mechanism based approach and utilizing the same ethical and rigorous methods such as are used to evaluate other pharmacological agents. Preliminary data on a mechanistic rationale for chemopreventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Randomized placebo control trials and the longterm follow-up and monitoring of patients and study participants are critical to meet the requirements of the US Food and Drug Association and to promote the acceptance of new agents into the marketplace. 92,93…”
Section: Current Approachmentioning
confidence: 99%
“…Randomized placebo control trials and the longterm follow-up and monitoring of patients and study participants are critical to meet the requirements of the US Food and Drug Association and to promote the acceptance of new agents into the marketplace. 92,93…”
Section: Current Approachmentioning
confidence: 99%
“…It is theorized by Kumar et al (2012) that consumption of isoflavones will produce a corresponding increase in plasma levels of isoflavones. This increase should result in modulation of serum steroid hormone levels and can be measured by an increase in serum estradiol and a decrease in free testosterone.…”
Section: Reduction In Prostate Cancer Progression: the Soy Supplementmentioning
confidence: 99%
“…Isoflavones, a potent proteasome inhibitor , produced moderate modulation of steroid hormones and stabilization or reduction of serum prostate‐specific antigen and reduced percentage of cells expressing Ki‐67 posttreatment with no toxicity . It was also observed that genistein downregulates androgen receptor (AR) expression and produces an increase in FOX01 activity, a pathway that may be more relevant in African American (AA) men . Significant increase in NF‐κB activity was reported in prostate cancer cells exposed to chemotherapy and radiation.…”
Section: Proceedingsmentioning
confidence: 99%